Vasoactive Intestinal Peptide (VIP) in COVID-19 Therapy-Shedding of ACE2 and TMPRSS2 via ADAM10 - Gutzler, Charlotte; Höhne, Kerstin; Bani, Daniele; Kayser, Gian; Fähndrich, Sebastian Wolfgang; Ambros, Michael; Hug, Martin J.; Rieg, Siegbert; Falcone, Valeria; MüllerQuernheim, Joachim; Zissel, Gernot; Frye, Björn C. (International journal of molecular sciences, 2025)
Patients infected with SARS-CoV-2 may develop mild respiratory symptoms but also Acute Respiratory Distress Syndrome (ARDS). Additionally, severe systemic inflammation contributes to morbidity and mortality. The SARS-CoV-2 virus enters the cell by binding to the angiotensin-converting enzyme 2 (ACE2) receptor, followed by cleavage by transmembrane serine protease 2 (TMPRSS2). Vasoactive intestinal peptide (VIP) is known for its immune-modulating effects by suppressing the release of pro-inflammatory cytokines and enhancing regulatory T-cells. Furthermore, it has been tested in SARS-CoV-2-related clinical trials. We set out to investigate its role in the setting of SARS-CoV-2 infection in vitro. Epithelial cells (CaCo-2) were stimulated with SARS-CoV-2 spike protein, treated with native VIP and analyzed to investigate the mRNA and surface expression of ACE2 and TMPRSS2, the enzyme activity of TMPRSS2 and the infection rate by a SARS-CoV-2 pseudovirus. VIP downregulated ACE2 and TMPRSS2 mRNA and surface expression. Beyond these direct effects, VIP mediates the shedding of surface-expressed ACE2 and TMPRSS2 via upregulation of a sheddase protease (ADAM10). Functionally, these dual mechanisms of VIP-mediated downregulation of proteins involved in SARS-CoV-2 cell entry resulted in a reduced infection rate by the SARS-CoV-2 pseudovirus. These data imply that VIP hampers viral entry mechanisms based on SARS-CoV-2 and the linkage to ADAM10 may stimulate research in other indications beyond SARS-CoV-2.